2020
DOI: 10.1001/jamanetworkopen.2020.1611
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitors and Immune-Related Adverse Events in Patients With Advanced Melanoma

Abstract: IMPORTANCE Since 2011, immune checkpoint inhibitors (ICIs) have been effective treatment options for advanced melanoma. Little is known about how risks of immune-related adverse events (irAEs) vary by ICIs. OBJECTIVE To compare the risk of irAEs across different treatment regimens for advanced melanoma using network meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 36 publications
(129 reference statements)
6
41
0
1
Order By: Relevance
“…This suggests that reduction of tumor size is a clinical marker for the development of irAEs. To further support that, early reports from lung cancer and melanoma patients demonstrated a similar correlation between the anti-tumor effect of ICI and the severity of the irAEs [16][17][18]. A proposed mechanism of irAEs is that ICI reduce the self-tolerance of central memory or tissue resident T cells leading to the infiltration of tissues [19].…”
Section: Discussionmentioning
confidence: 79%
“…This suggests that reduction of tumor size is a clinical marker for the development of irAEs. To further support that, early reports from lung cancer and melanoma patients demonstrated a similar correlation between the anti-tumor effect of ICI and the severity of the irAEs [16][17][18]. A proposed mechanism of irAEs is that ICI reduce the self-tolerance of central memory or tissue resident T cells leading to the infiltration of tissues [19].…”
Section: Discussionmentioning
confidence: 79%
“…Although immunotherapy is a targeted therapy and therefore it is better tolerated compared to common chemotherapy, it has been associated with the emergence of a new panel of dysimmune toxicities called irAEs [ 9 , 118 120 ].…”
Section: Immune-related Adverse Events To Immunotherapymentioning
confidence: 99%
“…To avoid such consequences, it is necessary to choose the safest dosage and frequency of administration of ICIs to patients, enabling the maximum effects with minimal toxicity to the body. In one study, researchers conducted a meta-analysis of RCTs for the treatment of progressive melanoma and found that using nivolumab, 3 mg/kg (3 milligrams of drug per kilogram of body weight) every 2 weeks, and pembrolizumab, 2 mg/kg every 3 weeks and 10 mg/kg every 3 weeks, the risk of serious irAEs is low [ 96 ]. In another article, researchers analyzed NSCLC patients who developed autoimmune encephalitis after using ICIs.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%